PERAN PREVENTIF KUA (KANTOR URUSAN AGAMA) DALAM PEMBINAAN HUKUM PERKAWINAN SEBAGAI UPAYA MEMINIMALISIR KONFLIK WARIS KELUARGA: ANALISIS YURIDIS-NORMATIF - Azka Amatillah; Fitria Agustin (PT. Saha Kreasi Indonesia, 2026)
This study investigates the preventive role of the Office of Religious Affairs (KUA) in administering marriage law to reduce inheritance disputes within families through a juridical-normative approach. The KUA's legal basis, as outlined in PMA No. 34 of 2016 and the Compilation of Islamic Law (KHI), makes it a source of legal certainty. A marriage certificate serves as the initial step in obtaining legal status as an heir, while marriage guidance and legal counseling contribute to avoiding confusion regarding joint property and denial of inheritance rights. The importance of this management is evident in the increasing number of inheritance cases in the Religious Courts (15-20% annually due to unregistered unregistered marriages or polygamy), and from the perspective of the maqasid sharia (hifz al-nasl, hifz al-mal), which can reduce disputes through early education. The conclusion emphasizes the KUA's new role as a preventive guide to foster legal awareness within families.